Study on Consultation in the Mental Health Service of a General Hospital in the Buenos Aires suburban Buenos Aires, Argentina - Marzano, Fernando J. (New Frontiers in Medicine and Medical Research Vol. 11, 2021)
From the current historical reality, precise objectives are imposed to clarify and disseminate the complex process of our authentic national culture and disseminate the complex process of our authentic national culture. The task is toto recognize the legacy of Dr. Ramón Carrillo in the conformation and updating of health programs and plans health programs and plans. Consultations in our hospital care center are problematic, among other things, because of the place they occupy in the Buenos Aires suburbs. Patients whose habitat, environment, economic or political conditions, which is to say the same thing, demarcate the emergence of the "social" as a context and as an incidence in the various psychopathological manifestations they present. Conditions that must be reviewed from our practice, clinical psychology, theoretical assessments, as finally in the clinical domain that our clinical practice examines. And from our clinic we observe the extreme restriction of the field of the word in the story of our patients. We have observed that the word does not keep any guiding principle and the dominance of addictions is frequent. We also noticed that the new technologies have an effect on the conformation of a marginal spectrum. Its problematic deserves that we question these practices without neglecting the political inscription that is sustained and the primacy of the dominant groups.